Whole Genome Sequencing Reveals Antimicrobial Resistance and Virulence Genes of Both Pathogenic and Non-Pathogenic B. cereus Group Isolates from Foodstuffs in Thailand - Phornphan Sornchuer; Kritsakorn Saninjuk; Sumet Amonyingcharoen; Jittiporn Ruangtong; Nattaya Thongsepee; Pongsakorn Martviset; Pathanin Chantree; Kant Sangpairoj (Antibiotics, 2024)
Members of the Bacillus cereus group are spore-forming Gram-positive bacilli that are commonly associated with diarrheal or emetic food poisoning. They are widespread in nature and frequently present in both raw and processed food products. Here, we genetically characterized 24 B. cereus group isolates from foodstuffs. Whole-genome sequencing (WGS) revealed that most of the isolates were closely related to B. cereus sensu stricto (12 isolates), followed by B. pacificus (5 isolates), B. paranthracis (5 isolates), B. tropicus (1 isolate), and “B. bingmayongensis” (1 isolate). The most detected virulence genes were BAS_RS06430, followed by bacillibactin biosynthesis genes (dhbA, dhbB, dhbC, dhbE, and dhbF), genes encoding the three-component non-hemolytic enterotoxin (nheA, nheB, and nheC), a gene encoding an iron-regulated leucine-rich surface protein (ilsA), and a gene encoding a metalloprotease (inhA). Various biofilm-associated genes were found, with high prevalences of tasA and sipW genes (matrix protein-encoding genes); purA, purC, and purL genes (eDNA synthesis genes); lytR and ugd genes (matrix polysaccharide synthesis genes); and abrB, codY, nprR, plcR, sinR, and spo0A genes (biofilm transcription regulator genes). Genes related to fosfomycin and beta-lactam resistance were identified in most of the isolates. We therefore demonstrated that WGS analysis represents a useful tool for rapidly identifying and characterizing B. cereus group strains. Determining the genetic epidemiology, the presence of virulence and antimicrobial resistance genes, and the pathogenic potential of each strain is crucial for improving the risk assessment of foodborne B. cereus group strains.